Evaluation of Subjective Assessment of Right Heart Size and Function Using Standard 2D‐Echocardiographic Recordings in Horses With and Without Pulmonary Hypertension - Julia N. vanSpijk; Hannah K. Junge; Christina Eberhardt; Natalie Wolf; Debora Vogt; Paula Zscherpe; Elena Herger; Manon Straub; Colin C. Schwarzwald (Journal of Veterinary Internal Medicine)
ABSTRACT Background Echocardiographic evaluation of right heart (RH) size and function in horses is challenging and relies on subjective assessment. Objectives Evaluate inter‐ and intra‐rater agreement of subjective assessment of RH size, RH function, and the presence of pulmonary hypertension (PHT) in horses. Assess subjective RH changes with and without PHT and the influence of observer experience. Animals Healthy horses (n = 30) and horses with Doppler measurements suggesting the presence or absence of PHT (n = 30 each). Methods Nine standard echocardiographic recordings were analyzed by experienced (n = 4) and inexperienced (n = 5) observers. RH size, RH function, pulmonary artery (PA) size and distensibility, and the presence of PHT were subjectively assessed as normal, mildly, moderately, or severely changed. Inter‐ and intra‐rater agreement was calculated using percentual agreement (% agree) and kappa (k). Sensitivity and specificity to detect PHT were calculated. Results Overall inter‐rater agreement in all observers was low with 61% perfect agreement and k of 0.21; it was higher in experienced observers (k = 0.34, 77% agree) than in beginners (k = 0.18, 52% agree). Intra‐rater agreement showed % agree > 80% in experienced observers (k = 0.35–0.76) and < 80% in beginners (k = 0.33–0.54). RH size and function were more commonly abnormal in the PHT group, with high specificity but low sensitivity to detect PHT. Conclusions and Clinical Importance Rater agreement of subjective RH assessment was low and influenced by observer experience. Subjective absence of RH changes does not allow ruling out PHT, while the presence of characteristic RH changes suggests PHT.